EFFICACY OF CHRONIC HEART FAILURE COMBINED THERAPY DURING PERLINDOL USAGE IN ELDERLY POST INFARCTION PATIENTS WITH PSYCHOSOMATIC DISORDERS - M. E. Statsenko; I. A. Tyschenko (Столичная издательская компания, 2016)
Aim. To study the efficacy and safety of reversible MAO inhibitor pirlindol (Pyrazidol) in elderly post infarction patients with chronic heart failure (CHF) and affective disorders.Material and methods. 60 patients with CHF of II-III NYHA class 3-4 weeks after myocardial infarction with and anxious and depressive disorders were involved into the study. The patients were randomized in two groups. Patients of the first group received standard therapy (bisoprolol, lizinopril, simvastatin, acetylsalicylic acid, nitrates and diuretcs as required) in combination with pirlindol for 12 weeks. Patients of the second group received standard therapy alone. The follow-up period was 6 months. At baseline and after 12 and 24 weeks of therapy psychosomatic status was examined with the Beck questionnaire and HADS scale. Quality of life (QoL) survey with the Minnesota, Seattle and MOS SF- 36 questionnaires were performed as well as ECG with assessment of heart rate variability (HRV) and echocardiography.Results. Pirlindol improved QoL and was effective in correction of anxious and depressive disorders in CHF patients. At the end of the follow-up period normal Beck scores were registered in 90% and mild depression scores - in 10% of patients in pirlindol group. At the same time all patients of control group had depressive disorders of different intensity. Significant increase of left ventricular ejection fraction was observed in pirlindol group vs control group (20,9 vs -2,5%). Heart morphometric parameters improved in both groups, but left ventricle size reduction was more prominent in pirlindol group (-10,69 vs -5,34%). According to the spectral and time indexes of HRV, pirlindol treatment led to normalization of autonomic balance. Sympathetic overdrive was observed in patients of the control group.Conclusion. In elderly patients with CHF after myocardial infarction pirlindol taken additionally to the standard therapy is well tolerated, effectively eliminate psychosomatic disorders, results in significant improvement of morphofunctional cardiac condition and decrease of sympathetic over activity. Pirlindol can be recommended for the management of mild and moderate depressive disorders in elderly patients with CHF.